Late Quaternary sedimentation in Kejser Franz Joseph Fjord and the continental margin of East Greenland - Jeff Evans; Julian A Dowdeswell; Hannes Grobe; Frank Niessen; Ruediger Stein; Hans-Wolfgang Hubberten; R J Whittington (PANGAEA, 2002)
The marine sedimentary record in Kejser Franz Joseph Fjord and on the East Greenland continental margin contains a history of Late Quaternary glaciation and sedimentation. Evidence suggests that a middle-shelf moraine represents the maximum shelfward extent of the Greenland Ice Sheet during the last glacial maximum. On the upper slope, coarse-grained sediments are derived from the release of significant quantities of iceberg-rafted debris (IRD) and subsequent remobilization by subaqueous mass-flows. The middle-lower slope is characterized by hemipelagic sedimentation with lower quantities of IRD (dropstone mud and sandy mud), punctuated episodically by deposition of diamicton and graded sand/gravel facies by subaqueous debris flows and turbidity currents derived from the mass failure of upper slope sediments. The downslope decrease of IRD reflects either the action of the East Greenland Current (EGC) confining icebergs to the upper slope, or to the more ice-proximal setting of the upper slope relative to the LGM ice margin. Sediment gravity flows on the slope are likely to have fed into the East Greenland channel system, contributing to its formation in conjunction with the cascade of dense brines down the slope following sea-ice formation across the shelf. Deglaciation commenced after 15,300 14C years, as indicated by meltwater-derived light oxygen isotope ratios. An abrupt decrease in both IRD deposition and delivery of coarse-grained debris to the slope at this time supports ice recession, with icebergs confined to the shelf by the EGC. Glacier ice had abandoned the middle shelf before 13,000 14C years with ice loss through iceberg calving and deposition of diamicton. Continued retreat of glacier-ice from the inner shelf and through the fjord is marked by a transition from subglacial till/bedrock in acoustic records, to ice-proximal meltwater-derived laminated mud to ice-distal bioturbated mud. Ice abandoned the inner shelf before 9100 14C years and probably stabilized in Fosters Bugt at 10,000 14C years. Distinct oxygen isotope minima on the inner shelf indicate meltwater production during ice retreat. The outer fjord was free of ice before 7440 14C years. Glacier retreat through the mid-outer fjord was punctuated by topographically-controlled stillstands where ice-proximal sediment was fed into fjord basins. The dominance of fine-grained, commonly laminated facies during deglaciation supports ablation-controlled, ice-mass loss. Glacimarine sedimentation within the Holocene middle-outer fjord system is dominated by sediment gravity flow and suspension settling from meltwater plumes. Suspension sediments comprise mainly mud facies indicating significant meltwater-deposition that overwhelms debris release from icebergs in this East Greenland fjord system. The relatively widespread occurrence of fine-grained lithofacies in East Greenland fjords suggests that meltwater sedimentation can be significant in polar glacimarine environments. The ice-distal continental margin is characterized by meltwater sedimentation in the inner shelf deep, iceberg scouring over shallow shelf regions, winnowing and erosion by the East Greenland Current on the middle-outer shelf, and hemipelagic sedimentation on the continental slope.
Supplement to: Evans, J et al. (2002): Late Quaternary sedimentation in Kejser Franz Joseph Fjord and the continental margin of East Greenland. Geological Society of London, Special Publications (Open Acess http://hdl.handle.net/10013/epic.15709.d008), 203, 149-179, https://doi.org/10.1144/GSL.SP.2002.203.01.09